Studi Fenomenologis pada Perempuan Dewasa Awal dengan Orang Tua yang Bercerai - Rani Sagita; Zakwan Adri (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study focuses on understanding the experiences of early adult women whose parents got divorced. The research emploed a qualitative method through a phenomenological approach. Purposive sampling was used to select participants who met specific criteria, namely early adult women aged 18–25 years, with a background of parental divorce that occurred at least five years ago, currently unmarried or not in a marital relationship, and willing to participate in the study. The data analysis technique applied in this research is Interpretative Phenomenological Analysis (IPA). Interviews were used as the method for collecting data from the participants. The findings of this study revealed six superordinate themes: family dynamics and the root causes of parental divorce, psychological and emotional impacts of divorce, coping strategies and adaptation processes, views on marriage, personal growth and future aspirations, and partners as new sources of emotional support.